DESIGN AND DEVELOPMENT OF SEAM WELDING FOR DIFFERENT ALLOYS - Sankapusala Anilkumar, Ganesh K, Nagesh N (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this project is to study and analysis various parameters which is involved in seam welding: The welding has mainly divided into two types one is fusion welding other one is pressure welding. In the pressure welding electrode is pressed against the weldment which has to be weld. The pressure welding furtherly divided in to resistance welding, smiths forge welding mechanical energy (Pressure) i.e., friction welding and chemical reaction welding. One of the most important welding are resistance spot, seam, percussion welding which are widely used in sheet metal industries. In this project we have concentrate on seam welding for different type of materials like AISI 1015 low carbon steel, nickel alloy and magnesium alloys, for analysis we have changed parameters like pressure of the electrode and welding time, whereas ANASYS have been used to determine the optimum process time